2020
DOI: 10.1002/acn3.51027
|View full text |Cite
|
Sign up to set email alerts
|

Impact of simultaneous subthalamic and nigral stimulation on dysphagia in Parkinson’s disease

Abstract: Objectives: Dysphagia is a frequent and highly relevant symptom in Parkinson's disease (PD) due to high associated morbidity and mortality. To compare the effect of simultaneous stimulation of the subthalamic nucleus (STN) and substantia nigra (SNr) with conventional STN-stimulation on swallowing function in Parkinson's disease. Methods: In this controlled, randomized, doubleblind, cross-over clinical trial, 15 PD patients were assessed with DBS switched off (STIM OFF), STN-DBS, STN + SNr-DBS. Patients and 32 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
0
14
0
1
Order By: Relevance
“…Parkinson disease Pharyngeal residue, 15,36-41,e19,e26-e30 sometimes reported in nearly all patients, 37,39 often reported as leading finding, [36][37][38][39][40][41] with predominance in the valleculae 37,38,e19,e30 Premature bolus spillage 15,38,e27-e30 Impaired swallowing reflex 47,e29,e30 Pharyngolaryngeal movement disorders 15,47,e29,e31 Rarely reported: impaired secretion management e27,e28…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parkinson disease Pharyngeal residue, 15,36-41,e19,e26-e30 sometimes reported in nearly all patients, 37,39 often reported as leading finding, [36][37][38][39][40][41] with predominance in the valleculae 37,38,e19,e30 Premature bolus spillage 15,38,e27-e30 Impaired swallowing reflex 47,e29,e30 Pharyngolaryngeal movement disorders 15,47,e29,e31 Rarely reported: impaired secretion management e27,e28…”
Section: Discussionmentioning
confidence: 99%
“…However, residue in the valleculae was the major dysphagia manifestation in PD, which is in line with the results of previous studies. [35][36][37][38][39][40][41] Possibly, oropharyngeal bradykinesia contributes to reduced bolus clearance with accumulation in the valleculae in PD. 15 The phenotype of residue with predominance in the sinus piriformis was seen only rarely in the present study and occurred mainly in medulla oblongata stroke and inclusion body myositis.…”
Section: Discussionmentioning
confidence: 99%
“…Results from studies on the effects of DBS on swallowing function are controversial. Twelve studies (3 Class II [48][49][50], 9 Class IV [51][52][53][54][55][56][57][58][59]) were retrieved from literature search. In the majority of the studies, DBS targeted the bilateral STN and was delivered with high frequency stimulation.…”
Section: Tablementioning
confidence: 99%
“…Two studies compared the stimulation of the STN with the stimulation of the GPi [48,55], while one study targeted the caudal zona incerta [57]. Another study compared bilateral stimulation in STN with the combined stimulation of STN and substantia nigra [50]. In one study, the stimulation was unilateral [55].…”
Section: Tablementioning
confidence: 99%
“…Kraus reported that at least three patients developed worsening dysphagia or new dysphagia after bilateral STN DBS in a group of 27 PD patients during a mean of 30 months follow-up, based on the assessment for adverse effect, with unclear medication state though (8). Add-on stimulation of substantia nigra reticular (SNr) to STN did not have beneficial effect (41). Worsening of the dysphagia could be related to the suboptimal placement of the DBS electrodes or suboptimal programming in some cases, as turning off or reprogramming of the DBS made the swallowing symptoms better or go away in these cases (42,43).…”
Section: Pd With Stn Dbsmentioning
confidence: 99%